1999
DOI: 10.1097/00005768-199904000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Early phase adaptations of muscle use and strength to isokinetic training

Abstract: The purpose of this study was to investigate the effect of short periods of isokinetic resistance training on muscle use and strength. Seven men trained the right quadriceps femoris muscles (QF) 9 d for 2 wk using 10 sets of 5 knee extensions each day. Isometric and isokinetic torques of QF were measured at six angular velocities. Cross-sectional areas (CSA) of QF were determined from axial images using magnetic resonance imaging (MRI). Transverse relaxation time (T2) and activated area of QF, which represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
168
1
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(189 citation statements)
references
References 26 publications
13
168
1
7
Order By: Relevance
“…These authors observed that 3 weeks of twice-daily KAATSU-walk training produced significant muscle hypertrophy (4-7% increase in muscle volume) and increased dynamic and isometric strength (8-10% increase) in the thigh muscles despite the very low intensity of the exercise. The magnitude of muscle hypertrophy and strength gains as well as the hypertrophic potential (percent change in muscle volume divided by the number of Skeletal muscle size and strength are increased following walk training with restricted leg muscle blood flow: implications for training duration and frequency training sessions) is comparable with previous results following HIT (Ahtiainen et al, 2003;Jones and Rutherford, 1987), although greater training effects following HIT have been reported (Akima et al, 1999;Bell et al, 1992;Seynnes et al, 2007;Tesch et al, 2004).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…These authors observed that 3 weeks of twice-daily KAATSU-walk training produced significant muscle hypertrophy (4-7% increase in muscle volume) and increased dynamic and isometric strength (8-10% increase) in the thigh muscles despite the very low intensity of the exercise. The magnitude of muscle hypertrophy and strength gains as well as the hypertrophic potential (percent change in muscle volume divided by the number of Skeletal muscle size and strength are increased following walk training with restricted leg muscle blood flow: implications for training duration and frequency training sessions) is comparable with previous results following HIT (Ahtiainen et al, 2003;Jones and Rutherford, 1987), although greater training effects following HIT have been reported (Akima et al, 1999;Bell et al, 1992;Seynnes et al, 2007;Tesch et al, 2004).…”
Section: Introductionsupporting
confidence: 80%
“…Determining the hypertrophic potential is a theoretical attempt to evaluate muscle growth per training session by dividing the percent change in muscle volume by the number of training bouts. Maximal-intensity training 3 times a week for 5 weeks results in significant increases in muscle size (5-6%) and a hypertrophic potential of 0.3-0.5% (Akima et al, 1999;Bell et al, 1992;Seynnes et al, 2007;Tesch et al, 2004). Studies that have incorporated high-intensity (but not maximal effort) resistance training (e.g., 80% 1-RM or 10-RM) and similar training frequencies produce similar hypertrophic responses (~5% increase in muscle size; Ahtiainen et al, 2003;Jones and Rutherford, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The change in strength in response to exercise which occurs in the ®rst few weeks after beginning a training program is thought to occur via changes in CNS, output to the motor units, as there is no change in muscle mass during this time (Akima et al, 1999). The CNS may respond to training by increasing neuronal ®ring rates, improving the recruitment of motor units in response to the signal to contract a muscle, and by increasing the innervation of muscle over time.…”
Section: Mechanisms Underlying Sarcopeniamentioning
confidence: 99%
“…The KEE was performed at the MRI facility to permit image collection immediately after exercise (1,2,6,7,14,21,(33)(34)(35). Subjects performed four sets of 10 repetitions of concentric (extension phase)-eccentric (flexion phase) contractions with a load equal to 50% of the 4 ϫ 10 RM with the use of a plate-loaded knee extension machine (Badger-Magnum, Milwaukee, WI).…”
Section: Subjectsmentioning
confidence: 99%
“…Motor unit recruitment is mainly used to increase force in large muscles, such as the quadriceps femoris (QF) and the biceps brachii (15,29). In the QF, it has been demonstrated that recruitment of musculus rectus femoris (RF) does not necessarily coincide with that of the three m. vasti during repetitive isometric or isokinetic knee extension exercise (KEE) (6,7,20,28,42). This may reflect the fact that the RF is biarticulate, whereas the three vasti are more clearly synergistic, acting only about the knee joint.…”
mentioning
confidence: 99%